2019
DOI: 10.1021/acs.jproteome.8b00604
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomics Analysis of Milk Protein-Derived Peptides Released over Time in the Preterm Infant Stomach

Abstract: Over the course of milk digestion, native milk proteases and infant digestive proteases fragment intact proteins into peptides with potential bioactivity. This study investigated the release of peptides over 3 h of gastric digestion in 14 preterm infant sample sets. The peptide content was extracted and analyzed from milk and gastric samples via Orbitrap tandem mass spectrometry. The relative ion intensity (abundance) and count of peptides in each sample were compared over time and between infants fed milk for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 49 publications
4
30
0
Order By: Relevance
“…These findings align with those of our previous studies of digestion via peptidomics, which indicated the continual release of peptides from human milk proteins over time in the infant stomach and, by implication, the continual degradation of intact milk proteins [ 45 ]. This finding also agrees with our previous work indicating that palivizumab is degraded by incubation in infant gastric and intestinal fluids (ex vivo digestion) [ 18 ].…”
Section: Resultssupporting
confidence: 91%
“…These findings align with those of our previous studies of digestion via peptidomics, which indicated the continual release of peptides from human milk proteins over time in the infant stomach and, by implication, the continual degradation of intact milk proteins [ 45 ]. This finding also agrees with our previous work indicating that palivizumab is degraded by incubation in infant gastric and intestinal fluids (ex vivo digestion) [ 18 ].…”
Section: Resultssupporting
confidence: 91%
“…The intensities of peptides from regions f169-179 and f195-211 in PM7d were significantly higher than those in other samples at the end of gastric digestion. In summary, more and higher intensities of peptides were identified from the regions (16-55, 95-110, and 195-210), which was consistent with previous works presenting peptidomics analyses of bovine and human milk protein-derived peptides during in vitro dynamic digestion or clinical trials [32,33]. Similar hydrolysis regions of α s1 -CN were observed in all of the samples at the end of gastric digestion, although differences in peptide profiles existed in different samples during 120 min of digestion.…”
Section: Peptides Released During Digestionsupporting
confidence: 91%
“…Overall, κ-CN exhibited rapid hydrolysis at the initial stage of digestion and minor changes during subsequent digestion. Several regions (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112)(113)(114), and 168-179) were found to be resistant to hydrolysis in all of the samples during digestion, suggesting that these regions were resistant to pepsin hydrolysis.…”
Section: Peptides Released During Digestionmentioning
confidence: 99%
“…40 Protective potential of MOM is not measured by milk composition alone. The interaction between MOM and infant may result in greater protection than is measured in the milk itself, with release of immunomodulatory and anti-infective peptides in the infant's stomach that exceed the number in the pre-fed MOM, 68 with higher peptide release in preterm MOM than term MOM. 46 Similarly, the interaction between MOM enzymes and the infant's saliva produce superoxide and hydrogen peroxide, which inhibit opportunistic pathogenic bacteria.…”
Section: Bioactive Componentsmentioning
confidence: 99%